A Sociological Take on Language Generative AI Tools - Tan Chee Shien , Victor (International Journal of Emerging Technologies in Learning (iJET), 2024)
Language represents the medium in which human experiences are uniquely encoded by how an individual processes and produces language. The development of generative artificial intelligence tools such as ChatGPT created a challenge in the context of education due to how humans, being humans, often employ tools in unconventional ways as hallmarks of our creativity and critical thinking. Efforts to resist the incursion of AI into academic work have evidently failed, as observable from how the Russell Group changed its stance from prior bans on AI to the current acceptance of AI to a large degree (4 July 2023). This acceptance created tremors for the longstanding traditions of knowledge acquisition and production, which many academics are paying increasing attention to. In a bid to better understand the impact of such acceptance, the study was carried out to investigate the impact of AI use for sociological work. Employing a pilot study of a pragmatic approach with 20 graduates, it was found that while there was an even distribution of preference between personal writing and AI writing, academic submission preferences scaled towards AI writing. Preference for AI writing for submission was noted to be twice that of personal writing, despite an even distribution of preference. Findings also noted the qualitative differences between personal writing (268 words with 84 unique words) and AI writing (250 with 10 unique words) in word range and unique words. The analysis notes significant differences in word range between personal writing (± 35.93) and AI writing (± 4.28), reflecting a convergence of writing rhetoric that proves to be largely detrimental to sociological developments. The discussion presents considerations in three dimensions: the challenge on education, the challenge on language education, and the challenge on the sociological lens.